The role of local authority in mitigating the effects of climate change :the Case of Chikomba District in Zimbabwe (2013) - Maponde, Budiriro J. (Midlands State University, 2014)
The climate change issue has become a topical issue at the international, national as well as the lowest echelons of the society that is in the various districts, wards and areas. The research was conducted in Chikomba district which lies in Mashonaland East Province. The people are facing a number of challenges which includes food insecurity, water scarcity and loss of livestock which has become a major issue of concern. The main worry is that the effects are falling on people with poor adaptation and mitigation capacities as well as capabilities hence the need to ascertain the role of local authorities in mitigating the effects of climate change on the part of the local inhabitants. A qualitative approach was adopted in this study and data was gathered through interviews with Chikomba Rural District Council personnel that are the councilors and management who were sampled through judgment sampling technique. Questionnaires were also administered to members of the community who were sampled using convenient sampling technique The study revealed that the major drivers of climate change in Chikomba District were carbon dioxide (which comes from veldfires, burning of garbage by local authorities, emissions from mining instruments as well as through deforestation), methane(which is coming from cow dung as well as garbage) and nitrous oxide(which is coming from fertilizer use).The effects of climate change in the district includes food insecurity, loss of livestock as well as the loss of wetlands. The climate change mitigation strategies that were proffered include conservation farming, water harvesting as well irrigation and the holistic land and livestock management. Therefore the conclusion made is that climate change is really taking place in the district and it is being driven by carbon dioxide, methane and nitrous oxide. The effects of it are being felt in all the spheres of life therefore the need to proffer the mitigation strategies so as to try and lessen the burden on the rural populace.